Effect of Integrated Feedback on Classroom Climate of Secondary School Teachers - Nilesh Kumar Patel (International Journal of Evaluation and Research in Education (IJERE), 2018)
This study aimed at finding out the effect of Integrated feedback on Classroom climate of secondary school teachers. This research is experimental in nature. Non-equivalent control group design suggested by Stanley and Campbell (1963) was used for the experiment. Integrated feedback was treatment and independent variable, Classroom climate was dependent variable and pre- Classroom climate, and Intelligence were considered as covariates. The sample of the study comprised of 77 secondary school teachers and 220 students studying in secondary classes from purposively selected four schools of Indore city. The data for Classroom climate, Job satisfaction and Intelligence were collected through standardized tools. One-way ANCOVA and 2X2 factorial design ANCOVA were used for data analysis. Hypotheses were tasted at level of significance with α = 0.05. It was found that the treatment has significant effect over Classroom climate when pre- Classroom climate was taken as covariate. The results also shown that Classroom climate was independent of the treatment when Intelligence and pre- Classroom climate were separately considered as covariates. In addition, classroom climate was also found independent of interaction between feedback and intelligence when pre – Classroom climate was taken as covariate.